eisfabrik: a composition for sextet - Shivers, Jeffery. (2017)
Abstract: eisfabrik is a composition scored for bass clarinet, bassoon, percussion, viola, violoncello, and double bass. It was premiered on November 9, 2015 in Distler Hall at Tufts University. This work explores various issues of time and the performance process through a unique set of musical devices. In this thesis, I discuss the specific techniques used to organize the piece, as well as less concrete inspirations behind its development.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Music.; Advisor: Shawn Jaeger.; Committee: John McDonald, and Frank Lehman.; Keyword: Music.